Production Potential Assessment of Biogas from Napier Grass Using Geographic Information - Khotmanee, Saran; Pinsopon, Unnat (My University, 2022)
Thailand 2015 Alternative Energy Development Plan declared that 1,280 MW of electricity, 1,283 ktoe equivalent of heat production, and 4,800 ton/day transport biofuel would be sourced from biogas by the year 2036. To understand the current situation, Thailand biogas production potential from Napier grass by region was investigated. Napier grass was assumed to be cultivated only on the unused land. Geographic information of land use and soil type was overlayed on the country map to identify suitable Napier grass cultivation areas. Annual accumulated precipitation of each province was also taken into account to calculate the Napier grass crop yield. The study shows that Napier grass could be cultivated in all parts of Thailand. At present the Napier grass crop yield and biogas production potentials are found to be 189,237,760 ton/year and 11,354 million m3/year, respectively.
Keywords: biogas; Napier grass; Thailand